Prognostični pomen srčnih biomarkerjev pri bolnikih s pljučno trombembolijo - Kmet Lunaček, Nina (Zdravniški vestnik, 2006)
Background Pulmonary thrombembolism represents a spectrum of clinical syndromes ranging from small embolism presenting with dyspnea alone to massivethrombembolism causing shock or cardiac arrest. Majority of patients with pulmonary thrombembolism present with normal blood pressure, however, some may rapidly deteriorate despite therapeutic anticoagulation with heparine. Identification of such patients by risk stratification is of utmost importance for the care of pulmonary thrombembolism. It has been known for several years that a strong corellation exists between the prognosis of acute pulmonary thrombembolism and the degree of right ventricular dysfunction. Recently, some cardiac biomarkers have shown to be a promising predictive factor in evaluating right ventricular dysfunction and consequently establishing the prognosis of the clinical course in submassive and massive pulmonary thrombembolism. In the article the most important recent studies arerepresented confirming the important role of cardiac biomarkers in connection with prognosis in acute pulmonary thrombembolism. The most important are troponins, B-type of natriuretic peptide (BNP) with its pro-types and myoglobin. Conclusions Elevated levels of troponins, in combination with echocardiographic signs of right ventricular dysfunction, arepowerful predictors of adverse events and early mortality in normotensive patients with pulmonary thrombembolism. Normal or only slightly elevated levels of brain natriuretic peptides identify favourable prognosis in patientswith pulmonary thrombembolism.
Keywords: Atrial Natriuretic Factor; cardiovascular disease; diagnostika; Echocardiography; Ehokardiografija; kardiovaskularne bolezni; Mioglobin; Myoglobin; Natriuretic Hormone; Natriuretični hormon; Pljučna embolija; Preddvorni, natriuretični faktor; Prognosis; prognostični dejavniki; Prognoza; Pulmonary Embolism; Srce, prekat desni, disfunkcija; srčni prekat; Troponin; Ventricular Dysfunction, Right